2021
DOI: 10.1007/s16024-021-00354-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nursing staff working hours on stress levels during the COVID-19 pandemic

Abstract: Background Working as a nurse means being able to provide high-quality care 24/7. Studies have shown that the average number of working hours per week is a significant predictor of stress and that the severity of the coronavirus disease 2019 (COVID-19) pandemic has increased the nurses’ stress levels. Objective The aim of this study was to investigate the influence of the nursing staff’s working hours during the COVID-19 pandemic on the perceived level of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…The results of multiple linear regression analysis showed that hospital level, weekly working hours, and occupational stress level affected the health status of the medical staff. The higher the health-facility level, the longer the working hours per week, the higher the level of occupational stress, and the worse the health status, consistent with relevant research results [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…The results of multiple linear regression analysis showed that hospital level, weekly working hours, and occupational stress level affected the health status of the medical staff. The higher the health-facility level, the longer the working hours per week, the higher the level of occupational stress, and the worse the health status, consistent with relevant research results [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the danger of infection, nurses' dedication to their work appears to be an innate desire to provide care for patients with COVID‐19 (Natividad et al, 2021 ). Nonetheless, the universal effort to control the outbreak leads to higher work hours and workload, which has been defined as the primary contributor to work‐related stress among nurses (Alenezi et al, 2018 ; Duarte et al, 2020 ; Hoedl et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Women tend to cluster in occupations such as healthcare, social work and hospitality, all of which were severely hit by the COVID-19 pandemic (OECD , 2020. In the healthcare sector, for instance, workers suddenly found themselves working in a high-risk profession due to increased exposure to COVID-19 and being exposed to prolonged working hours (Hoedl et al 2021). Unfortunately, we were unable to control for the employment sector in the present analysis, which would have been important as it may have confounded the relationship between gender and work-related stressors (Kreimer 2004;Kjellsson 2021).…”
Section: Plausibility Of the Findingsmentioning
confidence: 97%